Estandarización del proceso de producción de balanceados para tilapias en Balanceados Exibal - Chambo. - Suconota Tenecota, Edinson Javier (2024)
The main objective of this research study was to make a diagnosis and verification of processes, to propose an improvement in the standardization of the production process for tilapia. Balanceados Exibal, is a company with high operational trajectory located in the Chambo canton, its extensive experience in the search to improve its processes and offer quality products to its customers, have led to constant continuous improvement.. this being a new line in their processes, previously to find the need for research a SWOT matrix was developed, which provided key information about the process, however, there were weaknesses such as poor standardization, lack of diagrams and documentation and interruptions in production. For this reason, a diagnosis of the current situation of the company in terms of the process was made, quality tools were used to describe and evaluate each of the stages of the processes, through the application of an Ishikawa diagram by the 5M method, it was found that most of the causes are given in methods where there is a lack of adequate control in the processes, labor and documentation, giving way to the second objective, where a study of methods and times was conducted. In this study it was possible to obtain a superior knowledge of the process using tools such as the operations diagram, route diagram and analytical flow chart. In the time study, the determination of the standard time gave a result of 150.3 minutes equivalent to (02h30min18sec), which is the time it takes to produce one ton of tilapia feed. In addition, changes have been proposed with the objective of contributing to the solution of problems identified in this study. Finally, a methodological structure was developed to demonstrate the main objective of this research, which is the proposed standardization of the process through the use of detailed procedures and instructions that guide and plan each of the stages of the processes. The application of this methodological structure will allow the analysis and identification of future improvements in the tilapia feed production process.